FMNL1 promotes proliferation and migration of leukemia cells. Issue 3 (25th June 2013) - Favaro, Patricia; Traina, Fabiola; Machado‐Neto, João Agostinho; Lazarini, Mariana; Lopes, Matheus Rodrigues; Pereira, João Kleber Novais; Costa, Fernando Ferreira; Infante, Elvira; Ridley, Anne J.; Saad, Sara Teresinha Olalla
Abstract : FMNL1 regulates leukemic cell proliferation, clonogenicity, migration, and interaction with endothelial cells, supporting a potential role in leukemogenesis. Abstract : The human FMNL1 is expressed predominantly in hematopoietic cells and has been described previously as overexpressed in hematopoietic malignancies. However, it is not known whether FMNL1 contributes to leukemogenesis. Here, we investigate the FMNL1 function using two different human leukemia models: Namalwa and K562 cell lines. FMNL1 depletion reduced cell proliferation and colony formation in both leukemic cell types, as well as a decrease in the tumor growth of FMNL1‐depleted Namalwa cell xenografts. In addition, there was a decrease in migration and in TEM in FMNL1‐depleted Namalwa cells. FMNL1 endogenously associates with Rac1, and FMNL1 silencing resulted in an increased Rac1 activity. The reduced migration observed in FMNL1‐depleted cells was restored by inhibiting Rac activity. Our results indicate that FMNL1 stimulates leukemia cell proliferation as well as migration. This suggests that FMNL1 contributes to leukemogenesis and could act in part through Rac1 regulation.